Analisis Konten Media Sosial Twitter Sarana Pendidikan di Indonesia Study Kasus Ruang Guru - Randisa, Aziz Reza; nurmandi, achmad (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
Twitter users in Indonesia are one of the biggest twitter users in the World. The use of Twitter in Indonesia, is often used in various activities, one of which is in the field of education. The @ruangguru account is a twitter account that is used to deliver content related to the Teacher's Room application. In Indonesia, Ruang Guru is the largest educational platform that can be enjoyed by the people of Indonesia, so the research objective is to analyze @ruangguru's Twitter content as a means of education in Indonesia, and what form of content or twet delivered by the @ruangguru account to users and other communities. This type of research uses descriptive qualitative research, with data collection methods used, namely with data capture containing content from the @ruangguru twitter account, and then analyzed using the Nvivo 12 application. The results of the research address the social media content Twitter @ruangguru containing information as an alternative learning in encouraging the provision of educational facilities in Indonesia. Ruang Guru received a good response from active twitter users who followed the @ruangguru account in providing or expanding access to quality education through technology that is not limited by time and place and can encourage quality education in Indonesia.